Extremum problems in some subclasses of analytical functions of a limited type - Terpigoreva, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. М. Терпигорева. Экстремальные задачи в некоторых подклассах аналитических функций ограниченного вида V. Terpigoreva. Ekstremaliniai uždaviniai kai kuriose aprėžto pavidalo analizinių funkcijų poklasėse